Travel Plans for New Residential Developments: Insights from Theory and Practice - De Gruyter, Chris; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This thesis explores the use of travel plans for new residential developments as a tool for managing car use and encouraging the use of more sustainable forms of transport. It provides coverage of the scale of travel planning practice for new developments, industry perspectives on their development and implementation, and an assessment of their quality and effectiveness. It combines implementation theory and planning enforcement theory to identify opportunities to enhance the effectiveness of travel plans for new residential developments and to guide future travel planning practice. This thesis is useful and will appeal to both researchers and practitioners involved in transport planning for new residential developments.
Introduction -- Travel plans and their application to new developments -- Theoretical foundations -- Research methodology -- The scale of travel planning practice -- Actor perspectives -- Travel plan quality -- Travel plan impacts -- Opportunities to enhance impacts -- Conclusions.
Keywords: Transportation engineering; Traffic engineering; Sustainability; Transportation Technology and Traffic Engineering; Sustainability